Impact of Service Quality Dimensions on Satisfaction and Loyalty: A Cross-National Research on Internet Service Customers - AYDINLI, Cumhur; KILIC, Sukru (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The aim of this research is to study about the impact level of service quality dimensions such as empathy, responsiveness, assurance, reliability, and tangibles on satisfaction and loyalty of the internet service consumers. The research was performed between customers from Turkey and Georgia. ServQual scale was conducted to obtain the data and evaluated using SPSS. Regression analysis was performed in order to see the impact of dimensions on the satisfaction and loyalty. Furthermore, Independent Samples T Test was performed to see which country was more satisfied about internet service provision than one another.